2020
DOI: 10.3389/fgene.2020.00478
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Prognostic miRNA Signature and Potential Critical Genes in Colon Cancer

Abstract: This study aims to lay a foundation for studying the regulation of microRNAs (miRNAs) in colon cancer by applying bioinformatics methods to identify miRNAs and their potential critical target genes associated with colon cancer and prognosis. Data of differentially expressed miRNAs (DEMs) and genes (DEGs) downloaded from two independent databases (TCGA and GEO) and analyzed by R software resulted in 472 DEMs and 565 DEGs in colon cancers, respectively. Next, we developed an 8-miRNA (hsa-mir-6854, hsa-mir-4437, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 91 publications
1
28
0
Order By: Relevance
“…Highlighted in this work, ribosome targeting is a novel function of miR-16-5p that may explain the tumor-suppressor properties of this miRNA. This effect was found through searching in two independent databases, which have, previously, provided critical resources for the identification of actionable miRNAs in various types of cancer and in diet and in physical activity [ 37 , 38 , 39 , 40 , 41 ]. Moreover, studies over the past years have shown that ribosomes are heavily modified in malignancies in order to meet the increment metabolic needs of the cancer cell.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighted in this work, ribosome targeting is a novel function of miR-16-5p that may explain the tumor-suppressor properties of this miRNA. This effect was found through searching in two independent databases, which have, previously, provided critical resources for the identification of actionable miRNAs in various types of cancer and in diet and in physical activity [ 37 , 38 , 39 , 40 , 41 ]. Moreover, studies over the past years have shown that ribosomes are heavily modified in malignancies in order to meet the increment metabolic needs of the cancer cell.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the expression of miR-3677 is negatively associated with the survival of patients with HCC and that miR-3677 is one of the tumor-specific miRNAs in HCC (12)(13)(14)(15). In addition, the preliminary prognostic role of miR-3677 has been determined in colon cancer (16,17). As a novel miRNA, miR-3677-5p has not been previously reported in neoplasms, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 87%
“…These show that elevated RHAMM expression is characteristic of most cancers and prognostic of a poor outcome in many. For example, elevated RHAMM expression is an indicator of poor prognosis in breast cancer [ 119 , 120 , 121 ], multiple myeloma [ 122 ], oral squamous cell carcinoma [ 123 ], ovarian cancer [ 124 ], lung cancer [ 125 ], prostate cancer [ 126 ], colon cancer [ 127 ], and gastric cancer [ 128 ]. However, histology analyses of these human tumors reveal that RHAMM expression is heterogeneous, and high RHAMM expression is often limited to a small subset of cancer cells [ 119 ].…”
Section: Rhamm Multi-functions In Cancermentioning
confidence: 99%